Impact of Trade Creation and Trade Diversion in Asean-Japan Comprehensive Economic Partnership (AJCEP) - Aprilia, Gayatri Talita; Handoyo, Rossanto Dwi (Journal of Developing Economies, 2019)
This study uses a gravity model to analyze the impact of the ASEAN-JAPAN COMPREHENSIVE ECONOMIC PARTNERSHIP (AJCEP) agreement on total Indonesian exports and to analyze the occurrence of trade creation or trade diversion. The data used in this study is panel data, the time used in this study from 2000 to 2015 consisting of 16 countries. This result finds the coefficient value of the FTA dummy of 0.207. This positive relationship indicates that there is a trade creation in AJCEP member countries and non AJCEP members. So it indicates that the welfare of member states and non AJCEP members. Total GDP, real exchange rate is positively correlated and GDP per capita difference and distance are negatively related to total Indonesian exports. Keywords: ASEAN-Japan Comprehensive Economic Partnership, Gravity Model,Trade Creation and Trade Diversion.JEL Classification: G230, G400, O330